Chaotic neural network based mpeg-2 video encryption framework over wireless channel - Tariq Adnan Fadil (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2014)
In this thesis, chaos theory property is combined with artificial neural network to construct a cipher cryptography algorithn called a Chaotic Neural Network (CNN). The proposed system model framework is develop and modelled by embedding CNN inside video codec model to produce a secure and a compress bitstream. The proposed video coded model is designed and implemented based on MPEG-2 standard.